COMPARISON OF COMPUTER LOCAL BUSES - Čiževskis, Oskars; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The author in this work provides insight into computer local buses. Themes which are discussed is breakdown by functional significance, data bus, address bus, control bus, description of SATA, PCI Express, HDMI buses, Intel Matrix Storage Technology, Intel Turbo Memory with User Pinning. Also was made the conclusions.